PERANCANGAN BUKU ILUSTRASI BIOGRAFI DENGAN TEKNIK VECTOR SEBAGAI UPAYA MENGENALKAN SEJARAH CAK DURASIM KEPADA ANAK DI SURABAYA - Giwangkara, Gilang; Martono, Siswo; Yuan, Dhika (Jurnal Art Nouveau, 2017)
Abstract: In today's modern era children tend to be happy to follow new trends that make them interested in the culture of foreign country rather than the culture of the country itself. This is what makes our country culture rarely glimpsed by children, Arts Ludruk is one that has been inherited by Cak Durasim in the city of Surabaya, but not all people in Surabaya, especially children - children recognize the figure Cak Durasim. Children need to be introduced about the history of Cak Durasim in order to be more able to appreciate and awaken the patriot's soul about the arts of his own country. The purpose of Cak Durasim's history illustration book is to re-introduce the history of Cak Durasim to the children in Surabaya and to awaken the heroic soul. The research was conducted using qualitative research methods, with data collection techniques and through interviews, observation, documentation and literature study. By raising